"In-between" a rock and a "third space"? On the trouble with ambivalent metaphors of translation. Issue 1 (2nd January 2016) - Maitland, Sarah
ABSTRACT: Homi Bhabha's The Location of Culture (1994) made waves in translation studies. His theories of hybridity, third space and the in-between have been consistently present in the literature ever since. For scholars concerned with the ethics of translation vis-à-vis the cultural other, Bhabha's metaphors give expression to the notion of "writing back" to neocolonial hegemonies. Despite their allure, what has not been addressed is the extent to which their success is threatened by the agency of the translator as a writer. Where the power to write is exercised not by the other but by the translator on their behalf, resistance to hegemony is an ideal that can only be ventriloquized. Through the framework of translation practice, this article examines Bhabha's metaphor of hybridity and signals the methodological risks of imbricating his ideas uncritically within resistant translation discourse.